All-optical nonlinear activation function based on stimulated Brillouin scattering - Slinkov, Grigorii; Becker, Steven; Englund, Dirk; Stiller, Birgit (Nanophotonics, 2025)
Optical neural networks have demonstrated their potential to overcome the computational bottleneck of modern digital electronics. However, their development towards high-performing computing alternatives is hindered by one of the optical neural networks’ key components: the activation function. Most of the reported activation functions rely on opto-electronic conversion, sacrificing the unique advantages of photonics, such as resource-efficient coherent and frequency-multiplexed information encoding. Here, we experimentally demonstrate a photonic nonlinear activation function based on stimulated Brillouin scattering. It is coherent and frequency selective and can be tuned all-optically to take LEAKYRELU, SIGMOID, and QUADRATIC shape. Our design compensates for the insertion loss automatically by providing net gain as high as 20 dB, paving the way for deep optical neural networks.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Brillouin scattering; nonlinear activation function; nonlinear optics; optical fiber; optical neural network; optoacoustics; photonic neuromorphic computing

An optoacoustic field-programmable perceptron for recurrent neural networks - Becker, Steven; Englund, Dirk; Stiller, Birgit (Nature Communications, 2024)
Recurrent neural networks (RNNs) can process contextual information such as time series signals and language. But their tracking of internal states is a limiting factor, motivating research on analog implementations in photonics. While photonic unidirectional feedforward neural networks (NNs) have demonstrated big leaps, bi-directional optical RNNs present a challenge: the need for a short-term memory that (i) programmable and coherently computes optical inputs, (ii) minimizes added noise, and (iii) allows scalability. Here, we experimentally demonstrate an optoacoustic recurrent operator (OREO) which meets (i, ii, iii). OREO contextualizes the information of an optical pulse sequence via acoustic waves. The acoustic waves link different optical pulses, capturing their information and using it to manipulate subsequent operations. OREO’s all-optical control on a pulse-by-pulse basis offers simple reconfigurability and is used to implement a recurrent drop-out and pattern recognition of 27 optical pulse patterns. Finally, we introduce OREO as bi-directional perceptron for new classes of optical NNs.
CRIS-Team Scopus Importer:2024-04-26

Deep recurrent neural networks operations based on stimulated Brillouin scattering - Becker, Steven; Cabello, Jesús Humberto Marines; Englund, Dirk; Stiller, Birgit (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We experimentally demonstrate eight layers of a recurrent operator for photonic neural networks using stimulated Brillouin scattering. The programmable optoacoustic building block captures and processes coherently and frequency-selectively information without relying on artificial reservoirs.
CRIS-Team Scopus Importer:2024-10-04

High-Speed Coherent Photonic Random-Access Memory in Long-Lasting Sound Waves - Geilen, Andreas; Becker, Steven; Stiller, Birgit (ACS Photonics, 2024)
In recent years, remarkable advances in photonic computing have highlighted the need for photonic memory, particularly high-speed and coherent random-access memory. Addressing the ongoing challenge of implementing photonic memories is required to fully harness the potential of photonic computing. A photonic-phononic memory based on stimulated Brillouin scattering is a possible solution, as it coherently transfers optical information into sound waves at high-speed. Such an optoacoustic memory has shown great potential as it fulfills key requirements for high-performance optical random-access memory due to its coherence, on-chip compatibility, frequency selectivity, and high bandwidth. However, the storage time has so far been limited to a few nanoseconds due to the nanosecond decay of the acoustic wave. In this work, we experimentally enhance the intrinsic storage time of an optoacoustic memory by more than 1 order of magnitude and coherently retrieve optical information after a storage time of 123 ns. This is achieved by employing the optoacoustic memory in a highly nonlinear fiber at 4.2 K, increasing the intrinsic phonon lifetime by a factor of 6. We demonstrate the capability of our scheme by measuring the initial and readout optical data pulses with a direct and double homodyne detection scheme. Finally, we analyze the dynamics of the optoacoustic memory at different cryogenic temperatures in the range of 4.2-20 K and compare the findings to continuous wave measurements. The extended storage time is beneficial not only for photonic computing but also for Brillouin applications that require long phonon lifetimes, such as optoacoustic filters, true-time delay networks, and synthesizers in microwave photonics.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Brillouin scattering; cryogenics; nonlinear optics; optical memory; photonic neuromorphic computing

Implementation of an optoacoustic activation function based on stimulated Brillouin scattering - Becker, Steven; Storp, Jakob; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Artificial neural networks (ANNs) have emerged as powerful tools, which for example accelerate research on COVID-19. They solve challenging tasks by taking advantage of their self-learning abilities and nonlinearity [1, 2]. However, the freedom gained through the complexity of ANNs leads to computational intense model training, eventually consuming a lot of energy [3]. One possible solution to overcome the current issues could be by transferring ANNs into the optical domain. For instance, Shen et al. have demonstrated the rich capabilities of optical neural networks (ONNs) [4]. A key element of an ANN and ONN is its nonlinear activation function, however, only a few all-optical approaches are published. In addition, those published are frequency insensitive, limiting the maximum data bandwidth throughput.
CRIS-Team Scopus Importer:2024-12-16

Inter-vortex forward Brillouin scattering by chiral flexural phonons in twisted photonic crystal fibre - Zeng, Xinglin; Russell, Philip St. J.; Geilen, Andreas; Becker, Steven; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics, CLEO 2023, 2023)
We report forward stimulated Brillouin scattering between orthogonal circularly polarized vortex modes in chiral photonic crystal fibre. The interaction is mediated by cork-screw-like flexural phonons, which provide both linear and orbital angular momentum.
CRIS-Team Scopus Importer:2023-11-24

Order of Magnitude Increase in Storage Time of Photonic-Phononic Memory - Becker, Steven; Geilen, Andreas; Stiller, Birgit (2023 International Conference on Photonics in Switching and Computing, PSC 2023, 2023)
With the recent developments in photonic computing platforms, the need of novel optical memories becomes increasingly important. Optoacoustic memories have shown great potential due to their quick access time, coherent nature, and broad bandwidth. These continuously tunable memories can be controlled entirely optically, but so far their intrinsic storage time is limited by the acoustic life time to approximately 10 ns. In this work, we experimentally demonstrate a cryogenic optoacoustic memory with an intrinsic storage time beyond 135 ns.
CRIS-Team Scopus Importer:2023-12-15
Keywords: nonlinear optics; Optical computing; optical memory; stimulated Brillouin scattering

Photonic Activation Function Using Sound Waves - Slinkov, Grigorii; Becker, Steven; Englund, Dirk; Stiller, Birgit (2023 International Conference on Photonics in Switching and Computing, PSC 2023, 2023)
We experimentally demonstrate an in-fiber optoacoustic nonlinear activation function based on stimulated Brillouin scattering. The activation function can be tuned all-optically and shows an input-output behaviour of a LeakyReLU, Sigmoid, and quadratic function. Our scheme is coherent and frequency selective, which is suitable for operation in multi-frequency neural networks. In addition, the optoacoustic activation function can amplify its input signal, allowing to compensate on-the-fly for optical losses during propagation.
CRIS-Team Scopus Importer:2023-12-15
Keywords: neuromorphic computing; nonlinear optics; Optical neural networks; stimulated Brillouin scattering